Investigation into the infectivity and neutralisation profiles of diverse lyssaviruses using a pseudotyped virus system - Horncastle, Emma (2020)
Rabies is an encephalitic disease with a mortality rate that approaches 100% in the absence of treatment. The World Health Organisation recognises rabies as a neglected tropical disease due to its disproportionate impact on poor and vulnerable populations in developing countries. Whilst vaccines exist to help prevent and control rabies, these are not always available or accessible to those at high risk. Rabies currently can only be treated effectively prior to the onset of symptoms and as immunoglobulin treatments are expensive and in short supply, and current vaccines require multiple doses to reach full efficacy, full courses of post-exposure prophylaxis may not be completed, leaving vulnerable individuals at risk.